Simulation in the clinical setting: towards a standard lexicon - Glenn D. Posner (Advances in Simulation, 2017)
Abstract Simulation-based educational activities are happening in the clinical environment but are not all uniform in terms of their objectives, delivery, or outputs. While these activities all provide an opportunity for individual and team training, nuances in the location, timing, notification, and participants impact the potential outcomes of these sessions and objectives achieved. In light of this, there are actually many different types of simulation-based activity that occur in the clinical environment, which has previously all been grouped together as “in situ” simulation. However, what truly defines in situ simulation is how the clinical environment responds in its’ natural state, including the personnel, equipment, and systems responsible for care in that environment. Beyond individual and team skill sets, there are threats to patient safety or quality patient care that result from challenges with equipment, processes, or system breakdowns. These have been labeled “latent safety threats.” We submit that the opportunity for discovery of latent safety threats is what defines in situ simulation and truly differentiates it from what would be more rightfully called “on-site” simulation. The distinction between the two is highlighted in this article, as well as some of the various sub-types of in situ simulation.